Embodying imagined contact: Facial feedback moderates the intergroup consequences of mental simulation. (9th December 2013) - Bilewicz, Michal; Kogan, Aleksandra
<x xml:space="preserve">Abstract</x> Imagined contact is a fruitful strategy of improving intergroup attitudes. There are several mechanisms responsible for the effectiveness of such contact. This article presents a test of an affective mechanism of imagined contact by applying a facial feedback procedure. We used a physical blockade of the zygomaticus major muscle, known to constrain people's experience of emotional states. Participants imagining intergroup contact expressed more positive attitudes towards an outgroup when they could physically mimic a positive affective state by smiling, but there was no such effect when embodiment was constrained. The interactive effects on attitudes appeared due to greater perception of outgroup warmth. This study presents the first attempt to explain the role of embodiment in the improvement of intergroup relations.